Evaluasi Pembelajaran Menggunakan Model Charlotte Danielson Di SD Wonder Kidz - Ida Maskanah Ida Maskanah; Mawardi (Elementary School, 2023)
This study aims to evaluate the teacher’s performance in carrying out learning at Wonder Kidz Elementary School. This research is an evaluative study using the Charlotte Danielson model. Based on the Charlotte Danielson evaluation model, teacher performance evaluation can be assessed by covering four domains: (1) lesson planning and preparation, (2) classroom management (3), implementation of learning, and (4) professional responsibility. The subjects in this study were grade 1 to grade 3 teachers at Wonder Kidz Elementary School. The data collection techniques carried out include observation, document study, and interviews. In collecting research data using instruments with interview guides, questionnaires, and teacher performance assessment rubrics. Data validity test was carried out through source and technical triangulation techniques. The results of this study indicate (1) the teacher's performance in preparation and lesson planning is in the very good category (2) the teacher's performance in classroom management is in the very good category (3) the teacher's performance in carrying out learning is in the very good category (4) the teacher's performance in carrying out professional responsibilities is in the very good category.